2017
DOI: 10.2134/itsrj2016.06.0481
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Bentgrass (Agrostis spp.) to Postemergence Applications of Metamifop

Abstract: Previous research indicates that metamifop may be an alternative for the control of bermudagrass (Cynodon spp. Rich.) in bentgrass (Agrostis spp. L.) with minimal phytotoxicity; however, only a few cultivars have been evaluated for tolerance. We hypothesize that bentgrass cultivars will respond differently to increasing rates of metamifop. Therefore, the objective of our research was to evaluate the tolerance of several bentgrass cultivars to sequential postemergence applications of metamifop. ‘L‐93’, ‘Penn A‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This was less than the maximum injury of 38% to 74% caused by both rates of fenoxaprop, both quinclorac rates, and topramezone applied monthly (Table 2). Both Parker et al (2015) and Cooper et al (2017) reported similar results where multiple applications of metamifop at 0.2 kg ai ha −1 injured creeping bentgrass by less than 10%. Only one previous study has investigated repeated applications of siduron on creeping bentgrass putting greens.…”
Section: Creeping Bentgrass Response To Low-dose Herbicide Programsmentioning
confidence: 68%
See 1 more Smart Citation
“…This was less than the maximum injury of 38% to 74% caused by both rates of fenoxaprop, both quinclorac rates, and topramezone applied monthly (Table 2). Both Parker et al (2015) and Cooper et al (2017) reported similar results where multiple applications of metamifop at 0.2 kg ai ha −1 injured creeping bentgrass by less than 10%. Only one previous study has investigated repeated applications of siduron on creeping bentgrass putting greens.…”
Section: Creeping Bentgrass Response To Low-dose Herbicide Programsmentioning
confidence: 68%
“…Alternate approaches to control summer annual grassy weed infestations on golf putting greens could rely on postemergence herbicides. None are currently registered for use on creeping bentgrass putting greens, but some have shown promise for grassy weed control in other areas or have been assessed for turf tolerance on creeping bentgrass putting greens in published studies (Carroll et al 1992;Cooper et al 2017;Parker et al 2015). In creeping bentgrass mown to 0.6 cm, fenoxaprop, topramezone, and quinclorac are registered to control goosegrass, smooth crabgrass, or both depending on the product (Anonymous 2013(Anonymous , 2018b(Anonymous , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…ha –1 every 10 d for ultradwarf hybrid bermudagrass ( Cynodon dactylon × Cynodon transvaalensis Burtt‐Davy) cultivars ‘Champion’, ‘FloraDwarf’, ‘MiniVerde’, ‘MS Supreme’, and ‘Tifdwarf’, but only 46% clipping reduction for ‘TifEagle’. Furthermore, differences in tolerance have been reported among creeping bentgrass cultivars to the postemergence herbicides metamifop, fenoxaprop, and methiozolin (Cooper et al., 2017; Henry & Hart, 2004; Hoisington et al., 2014), which may result in variable responses to PGRs.…”
Section: Introductionmentioning
confidence: 99%